2013
DOI: 10.1111/geb.12130
|View full text |Cite
|
Sign up to set email alerts
|

Are cities different? Patterns of species richness and beta diversity of urban bird communities and regional species assemblages in Europe

Abstract: Aim To compare macroecological patterns between bird communities of European cities and regional species assemblages in the surrounding landscape, and to reveal geographical trends in the urbanization of native avifauna. Location Forty‐one towns and cities in continental Europe. Methods We compiled data on the species richness and community composition of urban avifauna from 41 European city breeding bird atlases, and of species assemblages comprising nine grid cells (each about 50 km × 50 km) from the EBCC At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 74 publications
10
98
2
4
Order By: Relevance
“…Among birds, urbanization decreases the distance decay of compositional similarity between cities [58,59]. In insects, 185 urbanization reduces beta-diversity because heterogeneous assemblages of specialists disappear from cities, while consistent suites of tolerant species persist.…”
Section: Urbanisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among birds, urbanization decreases the distance decay of compositional similarity between cities [58,59]. In insects, 185 urbanization reduces beta-diversity because heterogeneous assemblages of specialists disappear from cities, while consistent suites of tolerant species persist.…”
Section: Urbanisationmentioning
confidence: 99%
“…[65]. Effects like these may account for why, among European birds, urban species-area relationships are as steep as rural relationships [58]. 205…”
Section: Urbanisationmentioning
confidence: 99%
“…Cassey et al 2008). Although the homogenising effect of urbanisation may be evident at large geographical scales (Clergeau et al 2001;Ferenc et al 2014;Filloy et al 2015;Ibáñez-Álamo et al 2016;Murthy et al 2016), some studies have suggested that it may disappear at smaller regional scales (Jokimäki & Kaisanlahti-Jokimäki 2003;Kühn & Klotz 2006;Marchetti et al 2006;Sorace & Gustin 2008;Luck & Smallbone 2011;Tryjanowski et al 2015).…”
Section: Scale Dependence Of Biotic Homogenisation By Urbanisation: Amentioning
confidence: 99%
“…There are few studies of biodiversity in small cities, e.g. for plants (Wang et al 2014), birds (Ferenc et al 2014;Sorace and Gustin 2010;Helden et al 2012), fish (Peressin and Cetra 2014) and insects (Magura et al 2004;Elek and Lövei 2007;Helden et al 2012, ). Indeed there is a lack of review articles on this subject and many groups of animals have yet to be studied in terms of the effects of urbanization.…”
Section: Introductionmentioning
confidence: 99%